The Level of Knowledge of Undergraduate Medical Students on Initial Assessment of Trauma Patients at the Faculty of Medicine Udayana University - Syajida, Hanna; Sucandra, I Made Agus Kresna; Parami, Pontisomaya; Kurniajaya, I Gusti Agung Made Wibisana (E-Jurnal Medika Udayana, 2025)
Initial assessment represented a critical component in trauma management, aiming to reduce mortality and morbidity, particularly from respiratory failure and central nervous system injuries. Trauma remained a significant global health concern, with mortality rates surpassing those of chronic diseases. Its incidence increased globally, including in Indonesia. Medical students were expected to acquire competency in trauma assessment. This study evaluated the knowledge of undergraduate medical students at Udayana University regarding initial trauma assessment as foundational clinical preparation. This study aims to assess the knowledge level of medical students in the Bachelor of Medicine Program regarding initial trauma assessment at the Faculty of Medicine, Udayana University. This study uses a descriptive quantitative method with a cross sectional approach. The data is primary data collected through a questionnaire distributed to 95 students in the Bachelor of Medicine Program at the Faculty of Medicine, Udayana University. The study found that the majority of students had a low level of knowledge about initial assessment (60%), while 17.9% had moderate knowledge and 22.1% had good knowledge. Most respondents had never participated in BLS (76.8%) and ALS (90.5%) training. Students who participated in BLS and ALS training demonstrated better knowledge compared to those who did not participate in the training. The level of knowledge of students regarding initial assessment in trauma patients in the Bachelor of Medicine Program at the Faculty of Medicine, Udayana University, is still insufficient. Participation in trauma training significantly affects students' knowledge level. Keywords : initial assessment, trauma, basic life support, ABCDE, knowledge level